The Impact of Agile Methodologies and Cost Management Success Factors: An Empirical Study (Baghdad Science Journal, 2019)
Software cost management is a significant feature of project management. As such, it needs to be employed in a project or line of work. Software cost management is integral to software development failures, which, in turn, cause software failure. Thus, it is imperative that software development professionals develop their cost management skills to deliver successful software projects. The aim of this study is to examine the impact of cost management success factors with project management factors and three agile methodologies – Extreme Programming (XP), Scrum and Kanban methodologies which are used in the Pakistani software industry. To determine the results, the researchers applied quantitative approach through an extensive survey on 52 agile software development companies in Pakistan. Statistical techniques, such as Pearson’s correlation and mean and standard deviation were performed to examine the results. Following this analysis, we found that cost management has a positive effect on other project management factors, which are schedule, scope, risk, resources, and quality. Furthermore, it is determined that, in general, Kanban performed better than both, Scrum and XP in the context of project management factors.